Symbolic Exploration of Money For Kip-Kuliah Students as Educational Assistance Funds - Sriwahyuni, Sriwahyuni; Marissangan, Hasbi; Abdullah, Suparman; Latief, Iqbal (CV. Eureka Murakabi Abadi, 2025)
Underprivileged Indonesian students receive financial aid from the KIP-Kuliah program, therefore allowing access to higher education. Beyond their practical use, this study investigates how the money symbolically reflects optimism, social mobility, and personal development in the life of their beneficiaries. This study aims to explore the symbolic meanings that KIP-Kuliah recipients attach to the educational assistance funds they receive. It also seeks to understand how these meanings influence their identity, motivation, and perception of higher education as a pathway to social mobility. The research used is qualitative research with a phenomenological approach. Researchers will use questionnaires or interviews in data collection, so the data source is from respondents, namely sociology education students who received KIP-Kuliah. Based on the interview results, it can be concluded that students who are viewed as individuals who are academically and economically worthy of receiving assistance can strengthen their self-confidence both from their family, friends, and campus environment. The Kip-Kuliah Scholarship obtained by students can be a symbol of moral responsibility for both the individual scholarship recipient, their family, and their social environment. Although inclusive, Kip-Kuliah scholarship recipients indirectly mark the differences in social class among students. In certain interactions. This can cause feelings of inferiority or become a motivation to prove oneself. Through the perspective of symbolic interactionism, it is revealed that the meaning of money is formed and modified through the process of social interaction and students' life experiences.